Teacher Compensation and School Quality: New Findings from National and International Data. - Zhijuan Zhang; Deborah A. Verstegen; Hoe Ryoung Kim (Educational Considerations, 2008)
High quality education is critical to both the individual and the nation. At the country level, as Ireland’s minister for education and science, put it, “The never ending search for competitive advantage in the global knowledge economy has led all public policymakers to focus on education as a key factor in strengthening competitiveness, employment and social cohesion.”
Keywords: teacher; achievement; data; turnover; assessment; methodology; salaries; quality